2022
DOI: 10.1097/opx.0000000000001949
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Disparities in Risk Factors for Myopia among Han and Minority Schoolchildren in Shawan, Xinjiang, China

Abstract: SIGNIFICANCE:The ethnic differences in myopia rates, ocular dimensions, and risk factors between Han and non-Han schoolchildren observed in this study may help fill the knowledge gap about ethnic minorities and are important for China and other countries to address vision-related health inequalities among different ethnic groups.PURPOSE: This study aimed to investigate the risk factors of juvenile myopia and elucidate the disparities of risk factors among Han and non-Han school students in Xinjiang, China.METH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Previous studies from China and Japan revealed that poor sleep quality was related to an increased incidence of myopia; 14 , 29 thus, sleep quality demonstrated a potential risk factor for myopia incidence. An epidemiological study on multiple ethnic groups in Xinjiang revealed that longer sleep time was associated with lower myopia incidence; 30 however, several other studies do not support this observation. For example, a cross-sectional study in Singapore found that sleep quality, duration, timing, as well as specific sleep factors were not independently associated with myopia, SE, or AL.…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies from China and Japan revealed that poor sleep quality was related to an increased incidence of myopia; 14 , 29 thus, sleep quality demonstrated a potential risk factor for myopia incidence. An epidemiological study on multiple ethnic groups in Xinjiang revealed that longer sleep time was associated with lower myopia incidence; 30 however, several other studies do not support this observation. For example, a cross-sectional study in Singapore found that sleep quality, duration, timing, as well as specific sleep factors were not independently associated with myopia, SE, or AL.…”
Section: Discussionmentioning
confidence: 93%
“…In some studies, the prevalence of myopia in adolescents with more outdoor activities is lower than that in those with only indoor activities, and fewer outdoor activities ( 22 , 25 ). Some studies have also shown that environmental risk factors, especially longer periods of near-work, have a significant impact on the prevalence of myopia ( 26 , 27 ). Epidemiological surveys show that the prevalence of myopia among students from economically underdeveloped areas and rural areas is lower than that of students from economically developed areas and cities ( 28 , 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, a study conducted on the UK ALSPAC database presents a contrasting perspective, suggesting that the act of smoking during pregnancy by grandmothers actually diminishes the prevalence of early-onset myopia. [15][16][17] .The Singapore Myopia Risk Factor Cohort Study (STARS) also suggests that maternal smoking may affect ocular development via nicotinic acetylcholine receptors, thereby reducing myopia in children 18,19 ..The cross-sectional reports from different regions and age groups in China also support the view that smoking is bene cial to reducing myopia [20][21][22] . The Spanish prospective cohort study (SUN project) followed the relationship between alcohol intake and myopia over a 10-year period after graduation, and found that alcohol consumption was signi cantly associated with the prevalence of myopia.…”
Section: Introductionmentioning
confidence: 99%